Gaya Bahasa Pada Novel Garis Waktu Karya Fiersa Besari: Kajian Stilistika - Nurul Hindayani; Sri Suciati; Pipit Mugi Handayani (Morfologi : Jurnal Ilmu Pendidikan, Bahasa, Sastra dan Budaya, 2024)
This research was motivated by analyzing the use of language styles in the novel Garis Tiket by Fiersa Besari. Language style in writing literary works has an important role in fiction stories because it is one of the factors that can determine whether a literary work is good or bad. Therefore, the author uses an interesting language style to express his ideas. The novel timeline by Fiersa Besari is a fictional story that uses various forms of language styles and has its own characteristics. The formulation of the problem in this research is how the language style manifests itself in the novel Garis Tiket by Fiersa Besari. The aim of this research is to describe the form of language style in the novel Garis Tiket by Fiersa Besari. The research method used is qualitative descriptive research. Qualitative research was used to analyze the form of language style in the novel Garis Tiket by Fiersa Besari. The data source used in this research is the written data source in Fiersa Besari's second edition of the novel Garis Uangi in 2021, which consists of 211 pages. The data in this research are paragraphs in the form of all the words, phrases, clauses and sentences contained in the novel Garis Kunci by Fiersa Besari. Based on the results of research analysis of the form of language style in the novel Garis Zaman by Fiersa Besari, forty-seven data were found, including five data for simile language style, three data for metaphor, six data for epic parables, eleven data for personification, ten data for metonymy, four data for synecdoche. and allegories totaling eight data. The language style most often used in the novel Garis Analisa by Fiersa Besari is personification.